2022
DOI: 10.1080/21655979.2022.2054207
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor receptor 2 promotes the proliferation, migration, and invasion of ectopic stromal cells via activation of extracellular-signal-regulated kinase signaling pathway in endometriosis

Abstract: Endometriosis is defined as the presence of endometrial tissues with cancer-like features in extrauterine locations. Fibroblast growth factor receptor 2 (FGFR2) is a tyrosine kinase that is involved in cancer pathogenesis. This study aimed to determine the role of FGFR2 in endometriosis. A total of 29 pairs of ectopic and eutopic endometrial tissues were collected from women with endometriosis. Endometrial tissues from women with hysteromyomas were considered as normal controls. Primary ectopic stromal cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…These bacteria were also positively correlated to proinflammatory markers IL-1α ( p < 0.05, p < 0.05, p < 0.01, respectively) and IL-1β ( p < 0.05, p < 0.01, p < 0.01, respectively). Additionally, these bacteria were positively correlated to fibroblast growth factor 2 and FGF-2 ( p < 0.05, p < 0.01, p < 0.01, respectively), which has been associated with proliferation, migration, and invasion of ectopic stromal cells [ 62 ]. M. lornae and B. vaginale C were also positively correlated with IL-12 p70 ( p < 0.05, p < 0.05, respectively) and fractalkine ( p < 0.05, p < 0.05, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…These bacteria were also positively correlated to proinflammatory markers IL-1α ( p < 0.05, p < 0.05, p < 0.01, respectively) and IL-1β ( p < 0.05, p < 0.01, p < 0.01, respectively). Additionally, these bacteria were positively correlated to fibroblast growth factor 2 and FGF-2 ( p < 0.05, p < 0.01, p < 0.01, respectively), which has been associated with proliferation, migration, and invasion of ectopic stromal cells [ 62 ]. M. lornae and B. vaginale C were also positively correlated with IL-12 p70 ( p < 0.05, p < 0.05, respectively) and fractalkine ( p < 0.05, p < 0.05, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Activation of the ERK signaling pathway is able to promote the proliferation of tumor cells and enhance the processes of tumor cell migration and invasion (65)(66)(67)(68), all of which leads to an acceleration of tumor progression. PD98059 could exert a positive protective effect, as it can inhibit tumor cell proliferation, migration and invasion (66,(69)(70)(71). In addition, activation of the ERK pathway has been demonstrated to mediate cell apoptosis, and this effect can be blocked by PD98059 (61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…The FGFR2 gene encodes a protein that is a member of the fibroblast growth factor receptor (FGFR) family [ 27 ]. FGFR2 was shown to be involved in biological processes such as cell proliferation, migration, tube formation and anti-inflammation in previous studies [ 28 , 29 ]. Our data revealed that overexpression of FGFR2 restored hRMECs function under HG and miR-524-5p overexpression conditions.…”
Section: Discussionmentioning
confidence: 99%